Car-Parrinello molecular dynamics simulations of Na⁺–Cl⁻ ion pair in liquid water - Khalack, J.M.; Lyubartsev, A.P. (Condensed Matter Physics, 2004)
The aqueous solvation shell of a Na⁺–Cl⁻ pair is studied using Car-Parrinello molecular dynamics simulations. Water-mediated and contact states of the ion pair are investigated. The first hydration shell of the Na⁺ ion is found to be octahedral with one vacant position for both states. In the contact state one of the water molecules is substituted by the Cl⁻ ion. The first hydration shell of the Cl⁻ is less structured and strongly effected by the proximity of the Na⁺ in the contact state. The oxygen coordination numbers for Na⁺ and Cl⁻ are 4.9 and 5.6 for the water-mediated state, and 3.6 and 6.4 for the contact state. The corresponding hydrogen coordination numbers are 10.9 and 5.2; 9.2 and 3.9, respectively.